OBTAINING CHIMERIC VARIANTS HBcAg EXPOSING HIV-1 MPER FRAGMENTS - A. P. Rudometov; N. B. Rudometova; B. N. Zaytsev; L. R. Lebedev; A. A. Ilyichev; L. I. Karpenko (Сибирский научный медицинский журнал, 2019)
The HIV-1 epidemic is one of the most acute global health problems. For several reasons, an effective vaccine against this infection has not yet been created. Currently, an important direction in the development of a vaccine against HIV / AID S is the design of immunogens that would be able to induce antibodies that neutralize a high diversity of HIV-1 strains (bNAbs). One approach to creating such immunogens is the construction of chimeric virus-like particles (VLPs) exposing epitopes recognized by bNAbs. The aim of the study was to obtain and characterize chimeric VLPs based on HBcAg, exposing epitopes recognized by bNAbs 2F5 and 4E10. Material and methods. The producing strains of  chimeric HBcAg variants were obtained by transforming E. coli BL21 cells with recombinant plasmids carrying the HBcAg genes and containing insertions encoding bNAbs epitopes 2F5 and 4E10. Purification of recombinant proteins was performed using gel filtration on a sepharose CL-6B column. The ability of recombinant HBcAg to form virus-like particles was assessed using electron microscopy. Analysis of the antigenic properties of epitopes in the composition of chimeric variants of HBcAg was performed using immunoblotting. Results. A modified nucleotide sequence of the HBcAg gene was obtained, which included the introduction of unique restriction sites flanking the region of the main antigenic determinant of the core. Based on this genetic construct, three recombinant plasmids encoding chimeric HBcAg variants, including epitopes of bNAbs 2F5 and 4E10, were obtained. Using immunoblotting, it was found that epitopes recognized by bNAbs retain their antigenic properties after insertion into the HBcAg.